Simplifying procedures to increase competitiveness at in vitro propagation of the olive cultivar 'Galega vulgar' - Peixe, A. (2009)
With the aim to reduce fees of a micropropagation protocol for the Portuguese olive cultivar ‘Galega Vulgar’, expensive Difco Bacto-Agar® was replaced by commercial agar-agar, and the analysed data revealed no significant differences between the two agars, for both the explants multiplication rate and the rooting capacity. The replacement of the OM vitamin complex by Tonosol®, a commercial vitamin formulation, was also evaluated, and, for the two vitamin sources, both, the multiplication and the rooting capacity of the explants, didn’t present significantly different values. Concerning the OM basal media salts, trials were carried-out for its replacement by Substral®, a liquid commercial fertilizer. This replacement was unsuccessful, with the cultured explants presenting growth abnormalities and significantly lower multiplication rates. Even with low-cost culture media formulations, the use of semi-solid media for micropropagation it is always associated to high labour fees, due to the systematic sub-cultures. To overcome that problem, trials using the RITA® temporary immersion system, were also performed.